Experimental music since 1970 - Gottschalk, Jennie (New York ; London : Bloomsbury Academic, 2016)
What is experimental music today? Recent attempts to define or identify examples of experimental music have been cautious and subjective, offering very little guidance to anyone with an interest in this field of activity. Is experimental music a historical event that refers only to John Cage and his influence, or does it have a greater spread and longevity? The development of this musical practice over the last 45 years merits a fresh definition and discussion. An experimental approach is not identifiable in specific sounds or techniques, and its scope would be drastically limited if it were judged on the basis of social or aesthetic groupings or self-identifications of composers.
Defining features of experimental music. Introduction ; Indeterminacy ; Silence -- Scientific approaches. Acts of discovery ; Harmonic relations ; Playing with numbers ; Learning by making ; Finding hidden sounds -- Physicalities. The physicality of performance ; Resonant spaces ; Objects as instruments ; From shape to sound -- Perception. The position of the listener ; The perception of time -- Information, language, and interaction. Treatments of sonic information ; The sounds of living beings ; Language ; Interaction -- Place and time. Mappings ; Site-specific works ; Histories -- Advocates.
Includes bibliographical references (pages 283-285) and index.
Keywords: Music -- 20th century -- History and criticism; Music -- 21st century -- History and criticism; Avant-garde (Music)